4t=3t+10

Simple and best practice solution for 4t=3t+10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4t=3t+10 equation:


Simplifying
4t = 3t + 10

Reorder the terms:
4t = 10 + 3t

Solving
4t = 10 + 3t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-3t' to each side of the equation.
4t + -3t = 10 + 3t + -3t

Combine like terms: 4t + -3t = 1t
1t = 10 + 3t + -3t

Combine like terms: 3t + -3t = 0
1t = 10 + 0
1t = 10

Divide each side by '1'.
t = 10

Simplifying
t = 10

See similar equations:

| 5x+33y=58 | | 3(f+1)=-12 | | 2b-10=6 | | x*80=250 | | 10+2k=20 | | 8-3/4*0 | | -4h=-8 | | D/11=9/5 | | 22-3x-15=4x+2 | | 8-3/4*-4 | | -5/8(100) | | x(2x+5)=5 | | N-10=27 | | 5(2r-3)=r-2 | | 8-3/4*4 | | 31-17v=-14v+7 | | X+(200+X)=210 | | x-0.25=250 | | 4x+9=11x-3 | | 7x-16=4(2x-5) | | -16+12=-4(x+4) | | 3x+45y=525 | | 8-3/4x4 | | 4x-4=51 | | 8-3/44 | | (5x+2)(2x+1)=27 | | 2mn^3*-2nm^2= | | -2(x+1)=3x+8 | | y=8-3(2+3) | | 3 = c4– 1 | | 3y+12=-57 | | 3x+4yx=16 |

Equations solver categories